Food Estate Dalam Perspektif Politik Pertahanan Negara di Kabupaten Belu Provinsi Nusa Tenggara Timur - Syafruddin, Akhmad; Kamahi, Syahrin Badrin; Nami, Yohanes Jimmy; Baso, Boli Tonda (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2023)
Belu Regency, East Nusa Tenggara Province, is located in the border area of the Republic of Timor Leste and geographically has dry land that can be a threat of drought, causing low agricultural productivity and food scarcity. Food scarcity may lead to food vulnerability and disrupts national defense. The research aims to find out how far food estate as a state land strategy can solve the problem of food vulnerability in society. This research approach uses qualitative methods with a case study type. Data are collected through FGD, interviews, observation, and documentation. The research found that the food estate program in Belu Regency did not run well and was unable to solve food problems in Belu Regency. There are several reasons behind this result, such as technical factors of unpreparedness of production land and non-technical factors of socio-cultural transformation of society. However, from the national defense perspective, Food Estate can influence the security of the people in the RI-Timor Leste border region. In conclusion, the success of the Food Estate program in Belu Regency is highly dependent on collaboration between the local government and the community. It is because the national government has prepared all the supporting infrastructure. Several non-technical issues must be resolved through professional and ongoing assistance and training. Thus, the goal of self-sufficiency by 2024 can be reached.